Credit Scoring in the United States - Barbara Kiviat (economic sociology_the european electronic newsletter, 2019)
Credit scoring is the paradigmatic example of algorithmic governance (Fourcade and Healy 2017; Pasquale 2015). Corporations take information about thousands of individuals, data mine it for patterns that predict people not repaying their loans, and then make decisions about future lending-who gets money, how much interest they pay-based on variables that predicted default in the past.
Keywords: 300